1978
DOI: 10.1111/j.1600-0447.1978.tb06877.x
|View full text |Cite
|
Sign up to set email alerts
|

Gradual reduction of neuroleptic drugs among chronic schizophrenics

Abstract: Neuroleptic drugs were gradually reduced from 25 hospitalized chronic schizophrenics while 23 such patients were maintained on matched dosages of neuroleptics. At the end of 15 weeks, 74% of the drug-reduced subjects and 80% of the drug-maintained subjects were rated to have decompensated. Drug-reduced patients decompensated while receiving a mean of 75 mg equivalent of chlorpromazine. Clinical stability was obtained at 150 mg equivalent of chlorpromazine. Twenty-six percent of the drug-reduced patients showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Other studies, while more optimistic about outcome, have similarly demonstrated minimal differences in outcome between medicated and non-medicated patients (e.g. Carpenter, McGlashan & Strauss, 1977 ;Lonowski, Sterling & Kennedy, 1978;Manos, Taratsidis, Pappas & Routsoni, 1977;Nair, 1977;cf. Warner, 1985).…”
Section: (Ii) Predictive Validitymentioning
confidence: 91%
“…Other studies, while more optimistic about outcome, have similarly demonstrated minimal differences in outcome between medicated and non-medicated patients (e.g. Carpenter, McGlashan & Strauss, 1977 ;Lonowski, Sterling & Kennedy, 1978;Manos, Taratsidis, Pappas & Routsoni, 1977;Nair, 1977;cf. Warner, 1985).…”
Section: (Ii) Predictive Validitymentioning
confidence: 91%
“…Ravaris et al (1967) NAPrien et al (1968) Gallant et al (1975) - Quitkin et al (1978) - Lonowski et al (1978 Prange et al(1979) Rifkin et al(1979) Kane et al (1979) Schooler et al (1979) -Brown, Laughren (1981) -Branchey et al (1981) Shenoy et al (1981) Goldberg et al (1981) Herz et al (1982) -Van Kammen et al (1982) -Brown et al (1982) Kane et al (1982) Mandel et al (1982) Glazer, Sheard (1982) Lehman et al (1983) Kane et al (1983) -Carpenter, Henrichs (1983) -Lieberman et al (1984) Marder et al (1984) Angrist et al (1985) -Jayaram et al (1986) McMillan et al (1986) -Faraone et al (1986) -Nuchterlein et al (1986) -Lieberman et al (1986) -Davidson et al (1987) Farone et al (1987) -Kreisman et al (1988) -Boza et al (1988) -Van Kammen et al (1989) Herz et al (1989) Glazier et al (1990) -Buchanan et al (1992) -Sheinhauer et al (1992) Ventura et al (1992) -…”
mentioning
confidence: 99%